ANALYSIS OF THE CURRENT STATE OF THE PROBLEM OF FLIGHT SIMULATOR TRAINING OF CIVIL AVIATHION - L. N. Elisov; S. V. Gromov (Научный вестник МГТУ ГА, 2016)
The article deals with the problems of the simulator training of the crew of civil aviation. It is noted that the particular attention of the simulator training is paid to practising flying skills, though more complex activity remains out of the sphere of the estimation of the results of training.